Synthesis of fully bio-based diepoxy monomer with dicyclo diacetal for high-performance, readily degradable thermosets. (August 2019) - Yuan, Wangchao; Ma, Songqi; Wang, Sheng; Li, Qiong; Wang, Binbo; Xu, Xiwei; Huang, Kaifeng; Chen, Jing; You, Shusen; Zhu, Jin
Graphical abstract: Highlights: A fully bio-based diepoxy monomer with dicyclo diacetal was successfully synthesized. The cured diepoxy combined excellent degradability in acidic conditions with superior thermal and mechanical properties. The cured diepoxy kept stable in neutral and basic conditions even during hot-humid aging test. Abstract: Thermosets are very versatile owing to their high dimensional stability, chemical resistance and thermal and mechanical properties; however, they are difficult to be recycled or reworked because of their permanent cross-linked structure. In this paper, we synthesized a novel fully bio-based diepoxy monomer via acetalization of lignin derivative vanillin with bio-based polyol erythritol followed by reacting with bio-derived epichlorohydrin. Due to the degradability of dicyclo diacetal structure in the diepoxy monomer, the cross-linked epoxy network could be readily decomposed (completely dissolved in 1 M HCl solution at 50 °C within 40 min). While it was stable under neutral and basic conditions even during hot-humid aging test. Meanwhile, due to the rigidity of the dicyclo diacetal structure, it showed high glass transition temperature of 184 °C, and its modulus (4.7 GPa) and hardness (0.30 GPa) are even higher than those of conventional bisphenol A epoxy resin.